To simplify the expression 12 - (4 ÷ (4/3) + 1), we need to follow the order of operations (PEMDAS/BODMAS) which states that we should perform any calculations inside parentheses first, then exponents, then multiplication and division (from left to right), and finally addition and subtraction (from left to right).
First, we simplify the expression inside the parentheses:
4 ÷ (4/3)
To divide by a fraction, we multiply by its reciprocal:
4 ÷ (4/3) = 4 × (3/4) = (4 × 3) / 4 = 12 / 4 = 3
Now we can rewrite the expression: 12 - (3 + 1)
Next, we calculate within the parentheses:
3 + 1 = 4
Now we rewrite the expression: 12 - 4
Finally, we subtract:
12 - 4 = 8
Therefore, the simplified form of 12 - (4 ÷ (4/3) + 1) is 8.
simplify:
12 - 4 divided by 4/3 + 1
1 answer